Association Between Hospice Length of Stay, Health Care Utilization, and Medicare Costs at the End of Life Among Patients Who Received Maintenance Hemodialysis - Wachterman, Melissa W. (JAMA Intern Med, 2018)
IMPORTANCE: Patients with end-stage renal disease are less likely to use hospice services than other patients with advanced chronic illness. Little is known about the timing of hospice referral in this population and its association with health care utilization and costs. OBJECTIVE: To examine the association between hospice length of stay and health care utilization and costs at the end of life among Medicare beneficiaries who had received maintenance hemodialysis. DESIGN, SETTING, AND PARTICIPANTS: This cross-sectional observational study was conducted via the United States Renal Data System registry. Participants were all 770 191 hemodialysis patients in the registry who were enrolled in fee-for-service Medicare and died between January 1, 2000, and December 31, 2014. The dates of analysis were April 2016 to December 2017. MAIN OUTCOMES AND MEASURES: Hospital admission, intensive care unit (ICU) admission, and receipt of an intensive procedure during the last month of life; death in the hospital; and costs to the Medicare program in the last week of life. RESULTS: Among 770 191 patients, the mean (SD) age was 74.8 (11.0) years, and 53.7% were male. Twenty percent of cohort members were receiving hospice services when they died. Of these, 41.5% received hospice for 3 days or fewer. In adjusted analyses, compared with patients who did not receive hospice, those enrolled in hospice for 3 days or fewer were less likely to die in the hospital (13.5% vs 55.1%; P < .001) or to undergo an intensive procedure in the last month of life (17.7% vs 31.6%; P < .001) but had higher rates of hospitalization (83.6% vs 74.4%; P < .001) and ICU admission (54.0% vs 51.0%; P < .001) and similar Medicare costs in the last week of life ($10 756 vs $10 871; P = .08). Longer lengths of stay in hospice beyond 3 days were associated with progressively lower rates of utilization and costs, especially for those referred more than 15 days before death (35.1% hospitalized and 16.7% admitted to an ICU in the last month of life; the mean Medicare costs in the last week of life were $3221). CONCLUSIONS AND RELEVANCE: Overall, 41.5% of hospice enrollees who had been treated with hemodialysis for their end-stage renal disease entered hospice within 3 days of death. Although less likely to die in the hospital and to receive an intensive procedure, these patients were more likely than those not enrolled in hospice to be hospitalized and admitted to the ICU, and they had similar Medicare costs. Without addressing barriers to more timely referral, greater use of hospice may not translate into meaningful changes in patterns of health care utilization, costs, and quality of care at the end of life in this population.